Genome-wide scan of long noncoding RNA single nucleotide polymorphisms and pancreatic cancer susceptibility - Corradi, Chiara; Gentiluomo, Manuel; Gajdán, László; Cavestro, Giulia Martina; Kreivenaite, Edita; Di Franco, Gregorio; Sperti, Cosimo; Giaccherini, Matteo; Petrone, Maria Chiara; Tavano, Francesca; Gioffreda, Domenica; Morelli, Luca; et al. (International journal of cancer, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is projected to become the second cancer-related cause of death by 2030. Identifying novel risk factors, including genetic risk loci, could be instrumental in risk stratification and implementation of prevention strategies. Long noncoding RNAs (lncRNAs) are involved in regulation of key biological processes, and the possible role of their genetic variability has been unexplored so far. Combining genome wide association studies and functional data, we investigated the genetic variability in all lncRNAs. We analyzed 9893 PDAC cases and 9969 controls and identified a genome-wide significant association between the rs7046076 SNP and risk of developing PDAC (P = 9.73 × 10-9 ). This SNP is located in the NONHSAG053086.2 (lnc-SMC2-1) gene and the risk allele is predicted to disrupt the binding of the lncRNA with the micro-RNA (miRNA) hsa-mir-1256 that regulates several genes involved in cell cycle, such as CDKN2B. The CDKN2B region is pleiotropic and its genetic variants have been associated with several human diseases, possibly though an imperfect interaction between lncRNA and miRNA. We present a novel PDAC risk locus, supported by a genome-wide statistical significance and a plausible biological mechanism.
Keywords: senioři; Genetic Predisposition to Disease; celogenomová asociační studie; jednonukleotidový polymorfismus; Male; association study; výpočetní biologie; Carcinoma, Pancreatic Ductal; mikro RNA; inhibitor p15 cyklin-dependentní kinasy; Middle Aged; mužské pohlaví; studie případů a kontrol; nádory slinivky břišní; pancreatic cancer; single nucleotide polymorphism; MicroRNAs; duktální karcinom slinivky břišní; ženské pohlaví; Humans; Pancreatic Neoplasms; Cyclin-Dependent Kinase Inhibitor p15; lidé středního věku; RNA dlouhá nekódující; long noncoding RNA; genetická predispozice k nemoci; Computational Biology; Female; Aged; Genome-Wide Association Study; RNA, Long Noncoding; lidé; Case-Control Studies; Polymorphism, Single Nucleotide